Children wearing face masks to prevent communicable diseases: scoping review - Patrícia Pinto Braga; Meriele Sabrina de Souza; Patrícia Peres de Oliveira; Márcia Christina Caetano Romano; Gustavo Machado Rocha; Elaine Cristina Rodrigues Gesteira (Sociedade de Pediatria de São Paulo, 2022)
ABSTRACT Objective: To identify and synthesize scientific evidence that the use of face protection masks by children, in the community and at home, is a way of preventing communicable diseases. Data source: A scoping review was made using the Joana Briggs Institute method and PRISMA-ScR. A research was carried out in five electronic databases, at the Cochrane Library and on seven websites of governmental and non-governmental institutions. The data were organized in a spreadsheet and submitted to narrative analysis. Data synthesis: Initially, 658 productions were identified, of which 19 made up the final sample. Studies with higher levels of evidence are scarce. The types of masks identified were professional (surgical and facial respirators with filtration) and non-professional (homemade). The transmissible agents studied were influenza and SARS-CoV-2 viruses, and the evaluated environments were schools, homes and community spaces. The main discomforts reported were heat, shortness of breath, headache and maladjustment to the face. The indication and acceptability of masks change according to the age group and clinical conditions. There is no consensus on the reduction in the transmissibility of infections. Conclusions: Children older than five can benefit from the correct use of masks, as long as they are supervised, taught and educated to do so and the masks should be well adjusted to the face. The use of masks show better results when associated with other measures such as physical distancing, keeping places ventilated and frequent hand hygiene.